2014
DOI: 10.1007/s10103-014-1529-0
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity versus low-level laser therapy in the treatment of patients with knee osteoarthritis: a randomized controlled trial

Abstract: The aim of this randomized controlled study was to compare the effects of low-level laser therapy (LLLT) and high-intensity laser therapy (HILT) on pain relief and functional improvement in patients with knee osteoarthritis (KOA). A total of 53 male patients participated in this study, with a mean (SD) age of 54.6 (8.49) years. Patients were randomly assigned into three groups and treated with HILT and exercise (HILT + EX), LLLT and exercise (LLLT + EX), and placebo laser plus exercise (PL + EX) in groups 1, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
161
2
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(180 citation statements)
references
References 31 publications
7
161
2
10
Order By: Relevance
“…Seven studies 13,14,19,20,22,24,26 including 637 patients (334 LLLT and 303 placebo) assessed the WOMAC pain outcomes of the patients. The overall inverse variance pooled SMD calculated for WOMAC pain was -0.2 (95% CI; -0.42, 0.03).…”
Section: -2-womac Painmentioning
confidence: 99%
“…Seven studies 13,14,19,20,22,24,26 including 637 patients (334 LLLT and 303 placebo) assessed the WOMAC pain outcomes of the patients. The overall inverse variance pooled SMD calculated for WOMAC pain was -0.2 (95% CI; -0.42, 0.03).…”
Section: -2-womac Painmentioning
confidence: 99%
“…Low-power laser is recognized as an appropriate medical modality to treat knee osteoarthritis in animals and humans and can be used along with acupuncture or exercise [17]. Studies have shown that laser reduces inflammation [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…12,13 A meta-analysis has reported that LILT is ineffective for the treatment of LE. 5 On the other hand, HILT has been used for a wide range of disorders, including low back pain, 14,15 knee osteoarthritis, 16 facial paralysis, 17 and subacromial impingement syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…17 Kheshie et al 16 have reported HILT and LILT combined with exercise in knee osteoarthritis were effective modalities for decreasing pain and improving the knee function scores after six weeks of treatment. In that study, HILT and exercise therapy was found to be more effective than LILT and exercise therapy, and each of them was better than placebo laser and exercise therapy in patients with knee osteoarthritis.…”
mentioning
confidence: 99%